Research on Modal Analysis of the Spiral Bevel Gear System - Qian Lulu; Lou Peng; Zhang Huanzhang; Luo Jian (Jixie chuandong)
In this study, a spiral bevel gearbox of the aero-engine is taken as the research object. A method of gear system-level modal analysis of bevel gears is proposed. Based on the design parameters and machining parameters, a 3D model of spiral bevel gear pairs with accurate tooth surface is established. Then the static analysis of the gear pair is carried out to determine the normal contact of the gears. After that, the pre-stressed modal analysis is done to obtain the modal of the gear system. And the result is compared with the experimental data to verify the accuracy and effectiveness of the method. Finally, according to the engineering practice, the influence of different contact surfaces and loads on the system mode is analyzed. The results show that the pre-stressed modal analysis method based on accurate tooth surface can be used for modal analysis of the bevel gear system. The system mode has strong sensitivity to the contact surfaces but is weak to loads. That is to say, in a certain range, the influence of loads can be ignored, but the modal analysis of different contact surfaces is needed.